Environmental Problems in Coal Engineering in China under the Background of COVID-19 Epidemic and Their Countermeasures - Chengzhu He (Forest Chemicals Review, 1970)
Water pollution, air pollution and land pollution are the main environmental problems caused by coal engineering activities. Solving these problems is the main purpose of coal engineering environmental research. Through the methods of literature search and investigation, it is concluded that the consciousness control of science and technology on the manufacture of machinery and equipment, the implementation of engineering activities and the consciousness control on the final stage of engineering are the main reasons for the formation of environmental problems. Under general conditions, only in the coal engineering activities, the coal engineers realize the purpose of manufacturing machinery and equipment, the process of implementing engineering activities and the importance of the completion of the project. The study found that the coal engineering activists activities methods under the condition of COVID - 19 outbreak change, because people realize that life is supreme, the relationship between man and the environment of an organic whole, it is fundamentally get rid of the ideology of science and technology of recessive control laid a solid foundation, so as to thoroughly solve the environmental problems of coal activity provides a new path.